Back over there : one American time-traveler, 100 years since the Great War, 500 miles of battle-scarred French countryside, and too many trenches, shells, legends and ghosts to count - Rubin, Richard (St. Martin's Press, 2017)
The author of The Last of the Doughboys goes back to French battlegrounds of World War I to understand why memories of that war are so present in the minds and hearts of modern-day French people.